معيار الإثبات المتبع في البعثات الدولية الإنسانية لتقصي الحقائق - محده, عبد الباسط (University of Eloued جامعة الوادي, 2020)
يهدف المؤلف من هذه المقالة إلى تحديد معيار الإثبات المطبق في التحقيقات الدولية وبعثات تقصي الحقائق. في المقام الأول قمنا بالتعرف على معيار الإثبات المطبق في الإجراءات القضائية _الوسط التقليدي المعروف له_ على المستوى المحلي وعلى مستوى المحكمة الجنائية الدولية، حتى نعطي تصور شامل لمعيار الإثبات، وللوقوف على تطبيق معيار الإثبات في البيئة المقارنة. ثم من خلال تحليل تقارير مجموعة مختارة من لجان التحقيق وبعثات تقصي الحقائق شملت كل من لجنة خبراء يوغسلافيا، بعثة المفوضية السامية لحقوق الإنسان في العراق 2014، لجنة التحقيق الدولية المستقلة بشأن الجمهورية العربية السورية، قمنا بفحص معيار الإثبات المطبق في ممارسات اللجان. لنقوم بعد ذلك باستنتاج أربعة معايير للإثبات بدرجات يقين مختلفة. يتم استخدام هذه المعايير بشكل متفاوت فيما بينها، حيث حددنا أن معيار "الأسباب المعقولة للاعتقاد" يعتبر معياراً أساسياً لبعثات تقصي الحقائق، فهو الأكثر استخداماً، وتماسكاً للتطبيق في معظم الظروف. The main author’s aim for this article is to determine the standard of proof applied in international investigations and fact-finding missions. In the first place, we identified the standard of proof applied in judicial proceedings - The traditional environment is known to him - at the local level and at the level of the International Criminal Court, so as to provide a comprehensive perception of the standard of proof, and stand on the application of the standard of proof in the comparative environment. Then, through the analysis of the reports of a selected group of investigation committees and fact-finding missions, including the Yugoslav Committee of Experts, the OHCHR Mission in Iraq 2014 and the Independent International Commission of Inquiry on the Syrian Arab Republic, so ,we checked the standard of proof applicable to committee’s practices. Next, we deduce four standards of proof with different degrees of certainty. These standards are used in a varying manner among themselves, we have identified the "Reasonable reasons to believe" criterion is a basic standard for fact-finding missions. It is also considered the most used, coherent when applied in most conditions.
مجلد11، عدد3
Keywords: معيار الإثبات؛التحقيقات الدولية؛ تقصي الحقائق؛ لجان التحقيق؛ المحكمة الجنائية الدولية; The Standard of Proof; International Investigations; Fact-Finding Missions; Commissions of Inquiry ; International Criminal Court.